Globally-gridded data for manuscript: Global stocks and capacity of mineral-associated soil organic carbon - Georgiou, Katerina; Jackson, Robert B.; Vindušková, Olga; Abramoff, Rose Z.; Ahlström, Anders; Feng, Wenting; Harden, Jennifer W.; Pellegrini, Adam. F. A.; Polley, H. Wayne; Soong, Jennifer L.; Riley, William J.; Torn, Margaret S. (Zenodo, 2022)
Supporting globally-gridded data products for manuscript: Georgiou K., Jackson R. B., Vindušková O., Abramoff R. Z., Ahlström A., Feng W., Harden J. W., Pellegrini A. F. A., Polley H. W., Soong J. L., Riley W. J., Torn M. S. Global stocks and capacity of mineral-associated soil organic carbon. Nature Communications , 2022. We leveraged data from a global synthesis of soil fractionation measurements (DOI:10.5281/zenodo.5987415) along with ancillary data on climate, vegetation, and soil characteristics to produce spatially-explicit global estimates of mineral-associated soil organic carbon stocks (MOC) and mineralogical carbon capacity (MOC max ) in non-permafrost, non-desert mineral soils. Globally-gridded datasetsare givenin kgC/m 2 for topsoil (0-30cm) and subsoil (30-100cm)at 0.5 degree by 0.5 degree spatial resolution.